Miracles : a journalist looks at modern day experiences of God's power - Stafford, Tim (Minneapolis, Minnesota Bethany House Pub., 2012)
" A journalist explores claims of modern-day miracles to better understand how God is working in the world today" - Provided by publishers
Keywords: Miracles